Characterisation of Al2O3 doped hexanoyl Chitosan-LiCF3SO3-EC polymer electrolytes - Muhammad, F.H.; Subban, R.H.Y.; Majid, Siti Rohana; Winie, T.; Arof, Abdul Kariem (Springer Verlag (Germany), 2009)
The insolubility of chitosan in a wide range of organic solvents has limited the application of chitosan especially in electrochemical systems. In order to improve its solubility, acyl modification of chitosan was carried out in the present study. Films of hexanoyl chitosan-based polymer electrolyte were prepared by solution casting technique. The effect of filler on the transport properties of hexanoyl chitosan-LiCF3SO3-ethylene carbonate electrolytes has been investigated. The conductivity for filler-free polymer electrolyte is 2.75 x 10(-5) S cm(-1). The addition of 6 wt-% Al2O3 increased the conductivity by one order of magnitude to 1.01 x 10(-4) S cm(-1). Within the temperature range investigated, the conductivity of the polymer electrolytes are thermally assisted and can be described by Arrhenius law. The conductivity variant has been justified via the Rice and Roth model in which the number of free ions per unit volume, mobility and diffusion coefficient of free ions were obtained.